Textural characteristics, surface chemistry and oxidation of activated carbon - Daud, W.M.A.W.; Houshamnd, A.H. (2010)
Numerous researches were reviewed and interpreted to depict a comprehensive illustration of activated carbon and its behavior towards oxidation. Activated carbon as one of the most important adsorbents is tried to be described in this review paper by terms of its ``Textural Characteristics'' and ``Surface Chemistry''. These two terms, coupled with each other, are responsible for behavior of activated carbon in adsorption processes and in catalytic applications. Although as-prepared activated carbons are usually nonselective and their surfaces suffer from lack of enough reactive groups, their different aspects may be improved and developed by diverse types of modifications. Oxidation is one of the most conventional modifications used for activated carbons. It may be used as a final modification or as a pre-modification followed by further treatment. In this paper, methods of oxidation of activated carbon and other graphene-layer carbon materials are introduced and wet oxidation as an extensively-used category of oxidation is discussed in more detail.